"AKU" KARYA CHAIRIL ANWAR: MENGUNGKAP KRITIK SOSIAL MELALUI PENDEKATAN SEMIOTIK - JH. Fahrizal Nur Rizky; Aisyah Cahyani; Mohammad Regan Dwi Yulianto; Moh. Fikri Zulfikar (Jurnal Bastra (Bahasa dan Sastra), 2024)
This research aims to reveal social criticism in the poem “Aku” by Chairil Anwar through a semiotic approach. The scope of the research includes analysis of the meaning of signs in poetry as a representation of social criticism. The research method used is descriptive qualitative, with data collection techniques through repeated reading and recording important quotes from poetry. Data were analyzed using semiotic theory to capture hidden meanings in the text. The research results show that the poem “Aku” contains five main aspects of social criticism: (1) rejection of social status through the metaphor of a “bitch”, (2) dissatisfaction with social conventions that shackle individual freedom, (3) feelings of alienation and outcast that reflect dehumanizing treatment by society, (4) the spirit of resistance to oppression, and (5) apathy as a defense mechanism against suffering. An interesting finding from this research is how Chairil Anwar uses dark imagery and sharp language to convey a message of resistance and dissatisfaction with social norms that limit individual freedom. Through the poem “Aku”, Chairil Anwar not only created a moving literary work, but also voiced strong social criticism of the injustice and suffering experienced by society during his time. This poem invites readers to reflect on social conditions and the importance of change in order to achieve justice and individual freedom.